2011
DOI: 10.3109/13645706.2011.581291
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted transaxillary parathyroidectomy of an atypical adenoma

Abstract: The advancement of minimally invasive surgical technologies over the past several years has led to improved surgical outcomes and greater patient satisfaction. Particularly for patients undergoing parathyroidectomies, endoscopic surgeries resulted in smaller surgical scars when compared with the open approach. Early endoscopic methods, however, were still restricted in their ability to provide adequate dexterity, two-dimensional views of the operative field; and while smaller than open surgeries, still left th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Meticulous closure of subcutaneous tissues and skin was performed with fine attention to detail. Robotic-assisted parathyroidectomy with en bloc resection was performed as described previously [12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meticulous closure of subcutaneous tissues and skin was performed with fine attention to detail. Robotic-assisted parathyroidectomy with en bloc resection was performed as described previously [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Their ability to provide a magnified 3D view of the surgical area, hand-tremor filtration, fine motion scaling and precise multiarticulated hand-like motions has augmented the surgeon's technical skills and provided enhanced visibility of the recurrent laryngeal nerve (RLN) and parathyroid glands [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…In general, the ideal patient has some or all of the following characteristics: sporadic PHPT; signal gland disease, as suggested in preoperative ultrasonography and/or MIBI scan; a body mass index (BMI)<30; hypertrophic scars or keloid formation (particularly in young patients); no goiter; no previous radiation or surgical intervention in the neck region; no parathyroid carcinoma; no suspected multinodular goiter; and no cervical spinal disease [10,11]. Although previous reports show RTAPS is generally applied in cases of single, sporadic parathyroid adenomas, there are several reports of surgical cases that do not conform to the above criteria.…”
Section: Patient Selectionmentioning
confidence: 99%
“…After proper positioning, Noureldine et al [4] reported taking blood to measured baseline PTH levels. In some reports, the exact location of the lesion was visualized with USG before the initial incision [10,13].…”
Section: Operationmentioning
confidence: 99%
“…Robotic parathyroidectomy has been described lately by us and other groups in a few case reports and small series using an axillary incision [21,[27][28][29][30][31]. The robotic transaxillary approach permits a safe, precise, magnified dissection without the need for gas insufflation and has a better cosmetic result owing to the invisible scar in the neutral position.…”
Section: Introductionmentioning
confidence: 99%